2018
DOI: 10.3389/fphys.2018.00597
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Atypical Metalloproteinase Inhibitors Like Protein (Sbp8-1) From Scallop Byssus

Abstract: Adhesion is a vital physiological process for many marine molluscs, including the mussel and scallop, and therefore it is important to characterize the proteins involved in these adhesives. Although several mussel byssal proteins were identified and characterized, the study for scallop byssal proteins remains scarce. Our previous study identified two foot-specific proteins (Sbp7, Sbp8-1), which were annotated as the tissue inhibitors of metalloproteinases (TIMPs). Evolutionary analysis suggests that the TIMP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, the understanding of scallop byssus is still limited. Our previous study 10 12 demonstrated that the protein composition of scallop byssus is intriguing as well. Therefore, it is very interesting and important to dissect the key scallop byssal proteins.…”
Section: Introductionmentioning
confidence: 97%
“…However, the understanding of scallop byssus is still limited. Our previous study 10 12 demonstrated that the protein composition of scallop byssus is intriguing as well. Therefore, it is very interesting and important to dissect the key scallop byssal proteins.…”
Section: Introductionmentioning
confidence: 97%
“…Biochemical analyses and protein polymerization assays implied the potential cross-linker role of the most abundant metalloproteinase inhibitor (CF9441.24, e.g. Sbp8-1, Table S5 ) [20] . Furthermore, another 104 BRPs were classified into group 3, 28.7% of which were molluscan specific genes (ps level ≥ 9, Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the permanent adhesion of sessile bivalves (e.g., mussels), scallop remains the ability to discard its byssus instantly under certain adverse conditions, and to reattach to new substrates by rapid secretion of new byssus, which has been proposed as a key biological characteristic for its successful adaptation to various habitats [12] , [17] . Moreover, according to our previous study on Zhikong scallop Chlamys farreri (Jones et Preston, 1904) [17] , [18] , scallops can secrete more abundant byssus than mussels and possess distinct protein composition and unusual assembly mechanisms [17] , [19] , [20] , [21] . The unique adhesive characteristics of scallop byssus make it a valuable biological model to study the dynamic adhesive secretomic process of byssal detachment and reattachment.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence CGI_10005578 (EKC25384 | hypothetical protein) was annotated with Gene Ontology indicating a metalloendoproteinase inhibitor molecular function. Recently, a protein with a similar function was identified in the foot and byssus of Chlamys farreri [12,49]. In this species, the protein Sbp8-1, which was described as an atypical metalloproteinase inhibitor, is a component of the byssus that is probably involved in the binding between the different byssal proteins.…”
Section: Discussionmentioning
confidence: 99%